Enhanced Distillation Efficiency for Formic Acid Production: Simulation and Optimization with Aspen HYSYS - Fauzia, Farah; Sari, Dessy Agustina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This study investigates the simulation and optimization of the distillation column AT-660 at PT Chemical Happy, focusing on improving the efficiency and purity of formic acid production using Aspen HYSYS V10. Data collection involved operational conditions, component compositions, and flow rates from the plant, which were used to develop a detailed process model. The simulation assessed current performance and identified discrepancies between simulated results and actual data. Optimization runs identified key parameters, such as reflux ratio, feed location, and column pressure, that significantly impact separation efficiency and product purity. The results demonstrated enhanced performance of the distillation column, with increased formic acid purity and improved operational efficiency. The study highlights the practical applications of simulation software in industrial settings, providing actionable insights for process improvement and contributing to the development of more efficient and sustainable chemical engineering practices.